Deliverance in Ghanaian neo-pentecostal ministries : a critical assessment from an evangelical perspective - Ampong, Ebenezer Adu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2004